Evaluating the Effectiveness of a New Self-Centering Damper on a Knee Braced Frame. (29th March 2023) - Banihashem, Seyed Mohammad; Rezapour, Moein; Attarnejad, Reza; Sanei, Mahsa
Abstract : The use of shape memory alloys (SMAs) has been receiving increasing attention among researchers due to their special properties. One of the most important features of SMA is the superelastic behavior which causes the alloy to be able to remove all the applied deformation. This study is intended to evaluate the application of superelastic Nitinol in knee braced steel frames (KBF) as a damper. To fulfill the objective of this research, an experimental KBF system has been developed in ABAQUS using the microscopic finite-element method (FEM). The proposed superelastic damper is placed between the knee element and beam-column connection. Five SMA dampers with different stiffness are located in the KBF system and subjected to static cyclic loading. The hysteresis diagram obtained from this cyclic loading indicates that the damper increases the system strength. The greater the stiffness of the SMA damper, the higher the strength is. Furthermore, the superelastic alloy reduces the permanent deformation and the dissipation energy capacity of the KBF system. Totally, the SMA-equipped KBF system indicates a little lower energy dissipation capacity compared to the KBF system. However, based on the hysteresis diagrams, the reduction of residual deformation in all models is significant compared to the little reduction in energy dissipation. Therefore, the proposed SMA damper is capable of reducing the permanent deformation of the KBF system and maintaining the energy dissipation capacity at almost the same level, which is essential for keeping the structure stable.